(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2020)
Protecting security in cyberspace has become a priority for public authorities, which requires the development of adequate policies to prevent and counteract threats that materialize in the virtual world. The State is the main actor in the field of cybersecurity, without prejudice to the difficulty in delimiting actions in a space that, by definition, cannot be bounded across borders and jurisdictions. In decentralized states, the debate on the scope of the powers of sub-state entities in cybersecurity is raised, especially when regional and local governments, agencies and public services increasingly stand out as the object of malicious actions in virtual space. In Spain, the delimitation of powers between the State and the Autonomous Communities has been specified by the Constitutional Court in STC 142/2018, of December 20, in coherence with its doctrine and with the rational conception of the national security system.